Infection and innate immune mechanism of goose astrovirus - Xu, Linhua; Jiang, Bowen; Cheng, Yao; He, Yu; Wu, Zhen; Wang, Mingshu; Jia, Renyong; Zhu, Dekang; Liu, Mafeng; Zhao, Xinxin; Yang, Qiao; Wu, Ying; et al. (Frontiers in Microbiology, 2023)
Goose astrovirus (GAstV, genus Avian Astrovirus, family Astrovirus) was first discovered in 2005, but was not considered as a pathogen of gosling gout until 2016. Since then, goose astrovirus has erupted in Chinese goslings, causing at most 50% of gosling deaths. By December 2022, the disease had become epidemic and prevailed in goose farms in Jiangsu, Shandong, Anhui, Henan, Guangdong, Liaoning, Sichuan and other places in China. The disease mainly affects goslings within 3 weeks old. The typical symptoms of goose astrovirus are large deposits of urate in the viscera, joint cavity and ureter surface of infected goslings. Goose astrovirus infection can trigger high levels of iNOS, limiting goose astrovirus replication. The ORF2 domain P2 of the goose astrovirus activates the OASL protein, limiting its replication. Goose astrovirus can also activate pattern recognition receptors (RIG-I, MDA-5, TLR-3), causing an increase in MHC-Ia, MHC-Ib and CD81 mRNA, activating humoral and cellular immunity, thereby hindering virus invasion. Goose astrovirus also regulates the activation of IFNs and other antiviral proteins (Mx1, IFITM3, PKR) in the spleens and kidneys to inhibit viral replication. The innate immune response process in goslings also activates TGF-β, which may be closely related to the immune escape of goose astrovirus. Gaining insight into the infection and innate immune mechanism of goose astrovirus can help researchers study and prevent the severe disease in goslings better.